Hubungan Tingkat Pendidikan Orang Tua Terhadap Prestasi Belajar Siswa - Agus Supandi (Peneliti.net, 2019)
Education within the family is the main education. In the family are laid the foundations of educational norms. A solid foundation in education is in the family. Parental education influences the pattern of children's education at home. The purpose of this study is to find out the magnitude of the relationship between the level of education of parents to the learning achievement of students of class X IPS at Alihsan High School Bekasi. The research method used is a quantitative method. The results showed that there was a positive and significant relationship between the level of education of parents and the learning achievement of class X students at Alihsan High School.